WHY WE SHOULD TEACH GRAMMAR: INSIGHTS FOR EFL CLASSROOM TEACHERS - Setiono Sugiharto (Universitas Katolik Indonesia Atma Jaya, 2005)
Controversies about whether or not to teach grammar still reign in the current language pedagogy. Those who are against grammar teaching hold the view that grammar should not be taught since grammatical features can be acquired unconsciously in a natural setting. The protagonists of grammar teaching, however, argue that grammatical features need to be taught in order to facilitate the process of acquisition. Without questioning the legitimacy of the fact that grammatical features can be acquired unconsciously, this article argues that formal instruction is needed particularly in EFL contexts. Given this argument, the article addresses three important questions: (1) On what theoretical grounds should grammar teaching be based? (2) When should grammar instruction be given? and (3) How should grammar be taught? Keywords: the process of acquisition, grammatical features,formal instruction.